Oxidative status and histological changes in sea bass larvae muscle in response to high dietary content of docosahexaenoic acid DHA - Betancor, M. B.; Caballero, M. J.; Benítez-Santana, T.; Saleh, R.; Roo, J.; Atalah, E.; Izquierdo, M. (Journal of Fish Diseases, 2013)
In previous studies, we observed dystrophic alterations in muscle of 48-day-old sea bass fed imbalanced docosahexaenoic acid (DHA) and vitamin E diets. To understand the whole pathological process associated with oxidative stress, a histological study was performed by feeding 14-day-old sea bass larvae with microdiets containing different ratios of DHA/vitamin E (1/150, 5/150 and 5/300) for a period of 21days. Larvae fed diet 1/150 showed no lesions in contrast to larvae fed diets 5/150 and 5/300 where the highest incidence of muscle lesions and thiobarbituric acid reactive substances (TBARS) content was observed. Semithin sections revealed focal lesions consisting of degenerated fibres with hypercontracted myofilaments and extensive sarcoplasm vacuolization affecting both red and white muscle. Ultrathin sections of degenerating muscle fibres showed diffuse dilatation of sarcoplasmic reticulum, disorganized myofilaments and autophagic vacuoles containing myelin figures and dense bodies. Additionally, some macrophages were observed among injured fibres as numerous satellite cells. Results from the study agree with those obtained from previous work, proving the pathological potential of free radicals in sea bass larvae musculature. Moreover, high vitamin E inclusion could not completely protect cell membranes from free radicals action. 465 453 0,695 1,507 Q2 Q1 SCIE